Development of Balinese Dish Standard Recipes for a Fine Dining Projection Mapping - Adestya Ayu Armielia; Oqke Prawira; Savira Rizky Pradiati (Gastronomy Tourism Journal, 2023)
This study aims to develop standard recipes with Indonesian traditional dish to be served in a Fine Dining Restaurant that is aligned with the storyline and visual concept for a projection mapping project titled “Si Dulang”. Four Balinese courses from appetizer, soup, main course and dessert are chosen based on the origin, ingredients availability, color, and taste. The method applied in this study is descriptive qualitative approach with observation, literature studies, experiment, documentation. It is expected that Balinese dish may become a culinary icon for fine dining restaurant which can attract food lovers, food reviewer, and tourists to enjoy the new experience of eating, especially using projection mapping. The outputs of this research is the food product as well as the intellectual property right of the standard recipe module. The set menu may give additional value for the projection mapping project to leverage the customers’ dining experience.